Robot Arm Structure Design Using Polyamide Evaluated by Finite Element Analysis - Somyot Kaitwanidvilai; Siwawong Buthgate; Hisayuki Aoyama; Poom Konghuayrob (My University, 2020)
Robots have increasingly replaced humans for many jobs, including 24 h work, routine tasks, and dangerous jobs.However, the robot operating system has high power consumption in many processes.This has led to energy efficiency being the main focus.We have opted to build a robot with high strength, light weight, and low power consumption by reducing the weight of its components.Presently, we know that the structure of most robots in the world is made of metals, plastics, and composite materials.In this research, we designed the mechanical structure of robot arms with three different materials (cast iron, polyamide, and aluminum) using the finite element method to analyze and evaluate the possibilities of these materials.The dynamic load, power consumption, and mechanical characteristics were compared.It was found that polyamide could help lighten the weight by 40% and increase energy efficiency along with cost effectiveness by 41%.Although polyamide is particularly easy to find, cast iron is stronger than polyamide.
Keywords: Modular Robots and Swarm Intelligence